Organic metal and metalloid species in the environment: analysis, distribution, processes and toxicological evaluation ; [International Workshop on Organometallics in the Environment at the University of Essen in 2002 ; workshop proceedings supplemented with additional data] - Hirner, Alfred; Emons, Hendrik; Hirner, Alfred (Springer, 2004)
Subsequent to the profiling of organometal(loid) compounds in important biogeogenic and anthropogenic deposits, the importance of this class of compounds for human healthare evaluated by the analysis of both physicochemical and biological formation, distribution and transformation processes. Multidisciplinary articles writtenby experts from disciplines as diverse as biogeochemistry, ecotoxicology, analytical chemistry, microbiology and genetics estimate the global levels of biogeogenic and anthropogenic emissions of organometal(loid) compounds, and thusobtain an insight to processes which influence the genesis, as well as the distribution and stability of organometal(loid) species and their interaction with each other and other matrix compounds. The authors evaluate various environmentally relevant sources from a toxicological point of view, in orderto identify potential "hot spots" of organometal(loid)s, which can negatively influence ecosystems and human health. TOC:Organometallic Compounds in the Environment.- Advances in Analytical Methods for Speciation of Trace Elements in the Environment.- Analytical Strategies for Arsenic Speciation in Environmental and Biological Samples.- Occurrence and Speciation of Arsenic, Antimony and Tin in Specimens Used for Environmental Biomonitoring of Limnic Ecosystems.- Methylated Metal(loid) Species in Biological Waste Treatment.- Volatile Mercury Species in Environmental Gases and Biological Samples.- Biovolatilisation of Metal(loid)s by Microorganisms.- The Effect of Phosphate on the Bioaccumulation and Biotransformation of Arsenic(V) by the Marine Alga Fucus Gardneri.- Molecular Modeling Studies of Specific Interactions between Organometallic Compounds and DNA.- Organometal(loid) Compounds Associated with Human Metabolism.- Genotoxicity of Organometallic Species.- Current Aspects on the Genotoxicity of Arsenite and its Methylated Metabolites.- Cytogenetic Investigation in Employees from Waste Industries.- Neurotoxicity of Metals.- Actions of Metals on Membrane Channels, Calcium Homeostasis and Synaptic Plasticity.- Effects of Organometal(loid) Compounds on Neuronal Ion Channels
Includes bibliographical references and index
Keywords: Konferenzschrift; Aufsatzsammlung; Toxikologie; Metallorganische Verbindungen; Umwelttoxikologie; Chemische Analyse; Elementorganische Verbindungen